2010
DOI: 10.1186/1471-2431-10-87
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and behavioural correlates of oral hygiene status and oral health related quality of life, the Limpopo - Arusha school health project (LASH): A cross-sectional study

Abstract: BackgroundPromoting oral health of adolescents is important for improvement of oral health globally. This study used baseline-data from LASH-project targeting secondary students to; 1) assess frequency of poor oral hygiene status and oral impacts on daily performances, OIDP, by socio-demographic and behavioural characteristics, 2) examine whether socio-economic and behavioural correlates of oral hygiene status and OIDP differed by gender and 3) examine whether socio-demographic disparity in oral health was exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
54
6
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 32 publications
13
54
6
4
Order By: Relevance
“…Previously various studies have demonstrated that apart from diseases themselves, various sociodemographic and behavioral correlates of oral health status were present. 16 Indeed, it was concluded that "total tooth loss is a social-behavioral issue as much as it is disease related". 17 It was reported that there were associations between total tooth loss and low income, education, perceived poor oral health, smoking, and negative health behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously various studies have demonstrated that apart from diseases themselves, various sociodemographic and behavioral correlates of oral health status were present. 16 Indeed, it was concluded that "total tooth loss is a social-behavioral issue as much as it is disease related". 17 It was reported that there were associations between total tooth loss and low income, education, perceived poor oral health, smoking, and negative health behavior.…”
Section: Discussionmentioning
confidence: 99%
“…18 However, it was also concluded that the factors mentioned above may not be important in all populations. 16 Hemodialysis patients are very specific group of patients, entirely different from general population. They have various co-morbidities (high prevalence of cardiac diseases, anemia, hypertension, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…[17]. They have advised to adopt certain preventive strategies due to the high prevalence of calculus and plaque accumulation [3,17,18] .…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the oral health and practices among the people, the WHO (World Health Organization) have prioritized the importance of oral health by promoting in the schools. [17]. They have advised to adopt certain preventive strategies due to the high prevalence of calculus and plaque accumulation [3,17,18] .…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge, beliefs, and practices regarding PH are substantial determinants of future health status and quality of life [14,15]. Moreover, these components are related to productivity and performance and have a contributed to the general development of society [13,16].…”
Section: Introductionmentioning
confidence: 99%